Further Studies on Dehydration of Prawns in Rotary Drum Dryer - BALACHANDRAN, K. K.; BOSE, A. N. (Fishery Technology, 1968)
The paper deals with studies made to modify the process of drying of prawns in rotary drum dryer reported by the authors earlier. Prawns belonging to any species except M. monoceros can be satisfactorily dried. With M. monoceros invariably considerable adherence of shell occurs. Prawns of any size group can be dried provided in the case of medium and big size prawns they are beheaded prior to drying. In all size groups, beheading prior to drying results in better appearance of the end product in addition to the output of the dryer per charge being increased.